Dominant Arm Internal and External Rotation Strength is Related to Arm Pain in Youth Baseball Players - Jeffrey Paskewitz; Fred Breidenbach; Philip Malloy; P Michael Eckrich; Ryan Zarzycki (North American Sports Medicine Institute, 2024)
# Background and Purpose The prevalence of arm pain in youth baseball players is high with approximately half reporting arm pain during the season, and the number of ulnar collateral ligament reconstructions in youth baseball players is increasing. Few studies have examined the relationship between shoulder strength and passive range of motion (ROM) with arm pain (either shoulder or elbow pain) during throwing, especially in athletes in early adolescence. The purpose of this study was to determine the relationship between shoulder ROM and strength and the presence of arm pain during throwing in youth baseball players. It was hypothesized that less internal rotation (IR) ROM, less total rotational ROM, and lower IR and external rotation (ER) strength would be associated with arm pain. # Study Design Observational cohort study # Methods Sixty-five youth male baseball players between the ages of 12-15 were enrolled. Shoulder strength (ER, IR, ER/IR strength ratio, scaption) and passive ROM (ER, IR, flexion, horizontal adduction) were collected prior to the start of the spring 2021 baseball season. Players self-reported their arm pain frequency during throwing as never, rarely, sometimes, often, or always. The relationship between reported arm pain frequency during throwing and shoulder ROM and strength measurements was examined. # Results ER (ρ= -0.289, p=0.020) and IR strength (ρ= -0.262, p=0.035) were weakly and negatively correlated with reports of arm pain during throwing. No other clinical variables were associated with reports of arm pain (p ≥ 0.124) # Conclusion In youth baseball players, greater IR and ER strength were associated with less arm pain frequency during throwing, while ROM was not associated with arm pain frequency. Future research should explore these variables prospectively to determine if changes in ROM and strength are related to the development of arm pain in youth baseball players. # Level of Evidence 3